2011
DOI: 10.1097/wnf.0b013e318220d8c6
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Brain-Derived Neurotrophic Factor and Cortisol to Sulfate of Dehydroepiandrosterone Molar Ratio Associated With Clinical Response to l-Theanine as Augmentation of Antipsychotic Therapy in Schizophrenia and Schizoaffective Disorder Patients

Abstract: These preliminary results indicate that circulating BDNF and cortisol-to-DHEAS*100 molar ratio may be involved in the beneficial clinical effects of L-theanine as augmentation of antipsychotic therapy in schizophrenia and schizoaffective disorder patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…The studies were published from 2009 to 2015 and conducted in North America ( n = 3) [31,32,33], East Asia ( n = 2) [34,35], and the Middle East ( n = 1) [36]. Of the included six RCTs, only two studies [31,34] were performed under AC conditions and one [31] was under a two-arm control design, i.e., AC and PC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies were published from 2009 to 2015 and conducted in North America ( n = 3) [31,32,33], East Asia ( n = 2) [34,35], and the Middle East ( n = 1) [36]. Of the included six RCTs, only two studies [31,34] were performed under AC conditions and one [31] was under a two-arm control design, i.e., AC and PC.…”
Section: Resultsmentioning
confidence: 99%
“…The proportion of males was 68.9% ± 5.7%. Only two studies reported that the length of illness ranged from 9.3 ± 7.3 to 25.3 ± 9.6 years [34,36]. The mean antipsychotic daily dose in CPZ equivalent doses [37,38,39,40] varied from 258.9 ± 232.5 to 733.5 ± 432.5 mg.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, negative symptomatology, objective neurocognitive functioning, general functioning, quality of life and side effect prevalence did not differ in the groups. In terms of the mechanism of this supplement, circulating levels of neurochemical indicator brain-derived neurotrophic factor (BDNF) and cortisol-to-dehydroepiandrosterone sulphate (DHEAS)*100 molar ratio appear to be associated with the observed clinical improvements in schizophrenia symptoms, although the exact reason for this relationship is unclear [67]. Miodownik et al postulate that alterations in serum BDNF level and cortisol-to-DHEAS*100 molar ratio may mediate the beneficial effects of L-Theanine augmentation.…”
Section: Methodsmentioning
confidence: 99%
“…The proportion of males was 68.9% ± 5.7%. Only two studies reported that the length of illness ranged from 9.3 ± 7.3 to 25.3 ± 9.6 years [34,36]. The mean antipsychotic daily dose in CPZ equivalent doses [37][38][39][40] varied from 258.9 ± 232.5 to 733.5 ± 432.5 mg.…”
Section: Included Randomized Controlled Trials (Rcts)mentioning
confidence: 99%